In the Public Interest: A Discussion with Theda Skocpol about the Scholars Strategy Network - Deprez, Luisa; Fried, Amy (Maine Policy Review, 2012)
Luisa Deprez and Amy Fried interview Theda Skocpol about the Scholars Strategy Network (SSN). The SSN was founded to serve as a bridging organization to help university-based researchers and teachers to get involved in public debates and make their research and ideas accessible to fellow citizens, legislators, and journalists. The SSN includes scholars from many disciplines who share research about public policy issues, elections and civic life, as well as ideas for improvements in legislation and government practices.